Herstellung, Charakterisierung und Optimierung von austenitischen ODS Stählen - Gräning, Tim (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2019)
This book presents the processing and the characterisation of novel austenitic ODS steels and shows the impact of the selected processing parameters on the microstructure and the resulting mechanical properties. On the basis of the gained insights, an optimization of the material properties was achieved and a method to derive the mechanical properties from the microstructural characterization was established.